Implicit theories shape responses to social-evaluative threat - Ford, Máire B. (Frontiers in Psychology, 2023)
It is important to understand factors that make one more or less vulnerable to the harmful effects of social threat. This study focuses on the role of implicit theories (also referred to as mindsets) in shaping responses to a potent form of social threat, namely social-evaluative threat (SET). 124 individuals participated in an experimental study in which they were induced to have an incremental theory or an entity theory about their social skills. Next, they were exposed to SET in the laboratory. Psychological and physiological responses were assessed including social self-esteem, rumination, spontaneous mentions of concerns about one’s social skills, and heart-rate variability. Compared to those induced to have entity theories, those induced to have incremental theories were buffered from the typical harmful effects of SET on social self-esteem, rumination, and concerns about their social skills. The association between implicit theories and heart-rate variability fell just short of significance.